Strategi Komunikasi Internal Tim Kerja Kompetensi Dosen Dan Tendik Dalam Upaya Peningkatan Kompetensi Dosen Dan Tenaga Kependidikan (Studi Kasus Tim Kerja Kompetensi Dosen Dan Tendik) - Denti Oktaviani; Christoper Yudha Erlangga; Yan Bastian (PT. AHLAL PUBLISHER NUSANTARA, 2025)
Higher education in the era of globalization is required to produce superior human resources through competent lecturers and educational staff (tendik). The Directorate of Human Resources of the Ministry of Higher Education, Science, and Technology plays a crucial role in developing these qualities, one of which is through the Lecturer and Educational Staff Competency Working Group. However, the high intensity of the program demands an effective internal communication strategy to ensure optimal coordination. This study aims to determine the internal communication strategy implemented by the Lecturer and Educational Staff Competency Working Group in improving the competence of lecturers and educational staff. The method used is descriptive qualitative research with data collection techniques through non-participant observation, in-depth interviews, and documentation studies. Data analysis uses the interactive model of Miles and Huberman, which includes data reduction, data presentation, and drawing conclusions. The results show that the internal communication strategy implemented includes determining clear communication objectives, developing simple and easy-to-understand messages, utilizing formal and non-formal media, implementing vertical and horizontal communication patterns, and continuous evaluation through feedback. This strategy has been proven to support internship programs, certification, training, and laboratory innovation, thus having a positive impact on improving the competence of lecturers and education staff. Keywords: Internal Communication Strategy, Effective Communication, Lecturer Competence, Education Personnel. Abstrak Pendidikan tinggi di era globalisasi dituntut untuk melahirkan sumber daya manusia yang unggul melalui dosen dan tenaga kependidikan (tendik) yang kompeten. Direktorat Sumber Daya Kementerian Pendidikan Tinggi, Sains, dan Teknologi memiliki peran penting dalam mengembangkan kualitas tersebut, salah satunya melalui Tim Kerja Kompetensi Dosen dan Tendik. Namun, intensitas program yang tinggi menuntut adanya strategi komunikasi internal yang efektif agar koordinasi tetap berjalan optimal. Penelitian ini bertujuan untuk mengetahui bagaimana strategi komunikasi internal yang diterapkan Tim Kerja Kompetensi Dosen dan Tendik dalam meningkatkan kompetensi dosen dan tenaga kependidikan. Metode yang digunakan adalah penelitian kualitatif deskriptif dengan teknik pengumpulan data melalui observasi non-partisipan, wawancara mendalam, dan studi dokumentasi. Analisis data menggunakan model interaktif Miles dan Huberman, yang meliputi reduksi data, penyajian data, serta penarikan kesimpulan. Hasil penelitian menunjukkan bahwa strategi komunikasi internal yang dilakukan mencakup penentuan tujuan komunikasi yang jelas, penyusunan pesan sederhana dan mudah dipahami, pemanfaatan media formal dan nonformal, penerapan pola komunikasi vertikal maupun horizontal, serta evaluasi berkelanjutan melalui umpan balik. Strategi tersebut terbukti mendukung program magang, sertifikasi, pelatihan, dan inovasi laboratorium sehingga berdampak positif terhadap peningkatan kompetensi dosen dan tenaga kependidikan. Kata Kunci : Strategi Komunikasi Internal, Komunikasi Efektif, Kompetensi Dosen, Tenaga Pendidikan.